A simple electronic medical record system designed for research. Issue 3 (31st July 2021) - King, Andrew J; Calzoni, Luca; Tajgardoon, Mohammadamin; Cooper, Gregory F; Clermont, Gilles; Hochheiser, Harry; Visweswaran, Shyam
Abstract: With the extensive deployment of electronic medical record (EMR) systems, EMR usability remains a significant source of frustration to clinicians. There is a significant research need for software that emulates EMR systems and enables investigators to conduct laboratory-based human–computer interaction studies. We developed an open-source software package that implements the display functions of an EMR system. The user interface emphasizes the temporal display of vital signs, medication administrations, and laboratory test results. It is well suited to support research about clinician information-seeking behaviors and adaptive user interfaces in terms of measures that include task accuracy, time to completion, and cognitive load. The Simple EMR System is freely available to the research community and is on GitHub.